A reporter assay for the next generation of biomaterials: Porous‐wall hollow glass microspheres. (20th February 2014) - Cunningham, Aaron; Faircloth, Hunter; Jones, Matthew; Johnson, Christopher; Coleman, Tiffany; Wicks, George; Postma, Gregory; Weinberger, Paul
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The primary objective was to design a reporter assay to measure molecular release kinetics from a new porous‐wall hollow glass microsphere biomaterial with great potential in regenerative medicine and drug delivery. Second, future avenues for research will be discussed specifically in regard to potential clinical uses in laryngology. Study Design Basic science data report. Methods We developed an assay using fluorescent nanocrystals or quantum dots (Qdot 605) as a reporter. A Nuance FX multispectral imaging system was used to detect fluorescence in aqueous phase. Spectral output of known concentrations of aqueous Qdot 605 was measured by the Nuance system to create a standard curve. Results These data were plotted and fit to a curve. Qdot 605 emission demonstrates excellent correlation with concentration in a log‐log relationship [R2 = 0.99649, median error = 9.9%], indicating that the Qdot 605 assay is reliable and should be explored regarding its ability to evaluate the drug‐eluting properties of this material. Conclusions We have derived a method to measure Qdot concentration using fluorescent microscopy, which will facilitate future research on this exciting new biomaterial. This material has great potential for use in head and neck surgery. Specific avenues within laryngology to be investigated include laryngeal and tracheal reconstruction, vocal fold healing, and nerve regeneration. Furthermore, we believe this is the first documented use of the Nuance system to determine aqueous molecular concentrations. Level of Evidence NA Laryngoscope, 124:1392–1397, 2014